(untitled) (Revista Educação, Artes e Inclusão, 2025)
The Education Guidelines and Bases Law – LDB defines education as: “training processes that develop in family life, in human coexistence, at work, in teaching and research institutions, in social movements and civil society organizations and in cultural manifestations". also defines youth and adult education (EJA) as: Youth and adult education will be aimed at those who did not have access to or continued studies in primary and secondary education at the appropriate age and will constitute an instrument for lifelong education and learning . In other words, it is education for those who did not have it at their appropriate age. However, there are peculiarities in adult teaching, through bibliographical analysis and the author’s observations we will bring light to this type of teaching.